(untitled) (Russian Medical and Social Journal, 2019)
Introduction.Aortic valve stenosis is the most common valvular pathology in cardiac surgery patients: aortic valve stenosis correction surgery accounts for 10 to 22% of open-heart surgery. 30% of senile patients with severe aortic stenosis due to severe comorbidity and high operational mortality are denied prosthetics of the aortic valve under cardiopulmonary bypass. With the appearance of endovascular correction - minimally invasive surgical treatment methodsthe problem of choosing a method of correction of severe aortic stenosis in these patients arose. Objectives. To select a method for surgical correction of severe aortic valve stenosis in senile patients, determine the place of intra-aortic valvuloplasty in treatment, and create an algorithm for treatment of senilepatients. Patients and methods. The study included 122 patients >75 years old with severe aortic stenosis, confirmed by echocardiography (aortic valve area 40 mm Hg, peak velocity (aortic valve) >4.0 m/s), undergoing treatment at Cardiovascular Surgery Dept of the BurdenkoMain Military Clinical Hospital in 2010 – 2017. Due to the high surgical risk, patients of the first group (n = 89) underwent only conservative drug therapy, patients of the second group (n = 12) underwent prosthetic aortic valve replacement under cardiopulmonary bypass, and patients of the third group (n = 8) underwent balloon aortic valvuloplasty valve, after which 7 of them entered the fourth group, patients of the fourth group (n = 20) performed Transcatheter Aortic Valve Implantation . Results. In the maximum follow-up three-year period, the mortality rate in patients of the first group was 49.5%, the severity of heart failure in most of the surviving patients was at III-IV Class(NYHA); mortality in the second group of observation was 16.6%, there was a decrease in the severity of heart failure - the transition of most patients from III - IV to II Class (NYHA); in 7 out of 8 patients of the third group, after performing aortic valve valvuloplasty, hemodynamic stabilization was noted - in 5 patients there was a decrease in the manifestations of heart failure to III Class and in 2 patients - to II Class (NYHA), all of them entered the fourth group, in which, after performing TIAK the mortality was not notedduring the three-year observation of. Conclusions. In senile patients, surgical treatment of severe aortic stenosis is the method of choice and can significantly increase the one-year and three-year survival. In the group of senile patients with high surgical risk, endovascular correction of aortic stenosis is preferred. Balloon valvuloplasty of the aortic valve can be considered as a stage in the surgical treatment of severe aortic stenosis in patients with extremely high surgical risk. The next step in this group of patients should be performed transcatheter implantation of the aortic valve. The developed algorithm of a differentiated approach to the choice of a treatment method for severe aortic stenosis in senile patients allows a 32% increase (p